Diagnosis of mielomeningocele in a fetus through low field magnetic resonance. Case Presentation - Félix González Pérez; Yarely Águila Hernández; Victor Ibáñez Palacio; Lázaro Jiménez Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
The malformation in the neural canal (mielomeningocele) is a genetic disease characterized by a defect in the posterior wedge vertebral closing. Prenatal diagnosis is done by echography. A case of a 35 year old pregnant woman with 26 weeks of gestation is presented with a possitive result of alphafeto protein test and doubts in diagnostic ultrasound evaluating the possibility of a neural canal malformation. For these reasons it was suggested to perform a high field magnetic resonance. As high field resonance is not available, the parameters of low field were applied to this equipment (0.35 Tesla), which confimed the diagnosis. Neural canal malformations are not frequent therefore familial, personal, social and economical costs should be taken into consideration. It is important to diagnose them timely in order to administer the especific treatment. This is the foundation the case presentation importance, added to having achieved a certain diagnosis with a low field equipment.